Loss of Neuropilin2a/b or Sema3fa alters olfactory sensory axon dynamics and protoglomerular targeting - Ryan P. Cheng; Puneet Dang; Alemji A. Taku; Yoon Ji Moon; Vi Pham; Xiaohe Sun; Ethan Zhao; Jonathan A. Raper (Neural Development, 2022)
Abstract Background Olfactory Sensory Neuron (OSN) axons project from the zebrafish olfactory epithelium to reproducible intermediate target locations in the olfactory bulb called protoglomeruli at early stages in development. Two classes of OSNs expressing either OMP or TRPC2 exclusively target distinct, complementary protoglomeruli. Using RNAseq, we identified axon guidance receptors nrp2a and nrp2b, and their ligand sema3fa, as potential guidance factors that are differentially expressed between these two classes of OSNs. Methods To investigate their role in OSN axon guidance, we assessed the protoglomerular targeting fidelity of OSNs labeled by OMP:RFP and TRPC2:Venus transgenes in nrp2a, nrp2b, or sema3fa mutants. We used double mutant and genetic interaction experiments to interrogate the relationship between the three genes. We used live time-lapse imaging to compare the dynamic behaviors of OSN growth cones during protoglomerular targeting in heterozygous and mutant larvae. Results The fidelity of protoglomerular targeting of TRPC2-class OSNs is degraded in nrp2a, nrp2b, or sema3fa mutants, as axons misproject into OMP-specific protoglomeruli and other ectopic locations in the bulb. These misprojections are further enhanced in nrp2a;nrp2b double mutants suggesting that nrp2s work at least partially in parallel in the same guidance process. Results from genetic interaction experiments are consistent with sema3fa acting in the same biological pathway as both nrp2a and nrp2b. Live time-lapse imaging was used to examine the dynamic behavior of TRPC2-class growth cones in nrp2a mutants compared to heterozygous siblings. Some TRPC2-class growth cones ectopically enter the dorsal-medial region of the bulb in both groups, but in fully mutant embryos, they are less likely to correct the error through retraction. The same result was observed when TRPC2-class growth cone behavior was compared between sema3fa heterozygous and sema3fa mutant larvae. Conclusions Our results suggest that nrp2a and nrp2b expressed in TRPC2-class OSNs help prevent their mixing with axon projections in OMP-specific protoglomeruli, and further, that sema3fa helps to exclude TRPC2-class axons by repulsion from the dorsal-medial bulb.